2022
DOI: 10.1186/s12866-022-02537-7
|View full text |Cite
|
Sign up to set email alerts
|

(GTG)5-PCR fingerprinting of multi-drug resistant Escherichia coli bacteria isolates from hospital in Ouagadougou, Burkina Faso

Abstract: Background Escherichia coli (E. coli) is the most common bacterial species implicated in various types of infections including septicemia, gastroenteritis, urinary tract infections, meningitis and others pathologies. These involve several bacterial clones with multidrug resistance making them difficult to treat. The aims of this study was to perform molecular typing of E. coli strains using universal primer (GTG)5. In this study, 53 E. coli strains were collected from inpatients and outpatients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…High prevalence of uropathogens have been reported in sub-Saharan Africa (sSA) with 89.17% in Nigeria, 39.13% in Uganda, 10.1% in Ghana and 21.2% among children in Gambia [3]. These reports shown that most species belonged to Enterobacterales including Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Pseudomonas aeruginosa and were associated with numerous risk factors such as age, poor economic status, poor hygiene, hospitalization, catheterization, sexual activities, pregnancy and diabetes mellitus [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High prevalence of uropathogens have been reported in sub-Saharan Africa (sSA) with 89.17% in Nigeria, 39.13% in Uganda, 10.1% in Ghana and 21.2% among children in Gambia [3]. These reports shown that most species belonged to Enterobacterales including Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Pseudomonas aeruginosa and were associated with numerous risk factors such as age, poor economic status, poor hygiene, hospitalization, catheterization, sexual activities, pregnancy and diabetes mellitus [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…High prevalence of uropathogens have been reported in sub-Saharan Africa (sSA) with 89.17% in Nigeria, 39.13% in Uganda, 10.1% in Ghana and 21.2% among children in Gambia [3]. These reports shown that most species belonged to Enterobacterales including Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Pseudomonas aeruginosa and were associated with numerous risk factors such as age, poor economic status, poor hygiene, hospitalization, catheterization, sexual activities, pregnancy and diabetes mellitus [3][4][5].Emergence and escalation of extended-spectrum β-lactamase-producing E. coli and K. pneumoniae is aggravating the global concern of urinary tract infections. They are commonly associated with increased length of hospital stay, use of last-resort and often expensive drug and increase mortality [6].…”
mentioning
confidence: 99%
“…All strains collected in this study were MDR (non-susceptible to at least one agent in three or more antibiotic classes) [ 11 ]. Control strains, E. coli ATCC 25922, Klebsiella pneumoniae ATCC 700603, and Pseudomonas aeruginosa ATCC 27853, were included in every antibiotic susceptibility testing (AST) run [ 12 ]. All collected strains exhibited an MDR profile defined by the isolate being non-susceptible to at least one agent in ≥ three antimicrobial categories.…”
Section: Methodsmentioning
confidence: 99%
“…This means that Gram-positive and Gram-negative bacteria require different treatments. These carbapenemase and beta-lactamase-producing bacteria are common in West Africa 17 . However, the spread of Gram-negative bacteria producing carbapenemases and extended-spectrum beta-lactamases constitutes an “urgent” threat.…”
Section: Introductionmentioning
confidence: 99%